Hand hygiene practice among healthcare workers in intensive care units: a qualitative study - Hamid Ravaghi; Zhaleh Abdi; Ali Heyrani (Tehran University of Medical Sciences, 2015)
Abstract Background: Hand hygiene is the simplest and most effective preventive measures to reduce cross infection in hospitals. However, compliance with recommended instructions is commonly poor among healthcare workers. The present study aimed to explore potential behavioral determinants of hand hygiene compliance among healthcare workers in intensive care units. Methods and Materials: A qualitative study was conducted, consisting of 42 semi-structures interviews with physicians (attending physicians, non-attending physicians, residents), nurses, nursing students and medical students, who worked in the intensive care units. Results: Participants mentioned self protection as the main reason for the performance of hand hygiene. According to the participants, hand hygiene was often performed after direct contacts and tasks that were perceived to be dirty. Participants were most concerned about knowledge gaps in hand hygiene practice. Most participants believed that having a good theoretical knowledge of hand hygiene guideline may strengthen healthcare workers' attitudes toward hand hygiene. Junior practitioners believed that the superiors' hand hygiene practice could influence their performance both negatively and positively. Participant also believed that the lack of formal and informal control may hinder compliance among healthcare workers. High workload, interruptions, and limited access to hand hygiene products were mentioned as primary barriers to hand hygiene. Conclusion: The findings revealed that a number of factors can influence had hygiene practice. Recommendations of the current study are of value to future researches aiming to improve compliance with hand hygiene behavior among healthcare workers.